Additional file 5 of SIGIRR deficiency contributes to CD4 T cell abnormalities by facilitating the IL1/C/EBPβ/TNF-α signaling axis in rheumatoid arthritis - Xiu Teng; Da-Chao Mou; Hui-Fang Li; Ling Jiao; Sha-Sha Wu; Jin-Kui Pi; Yan Wang; Meng-Li Zhu; Meng Tang; Yi Liu (figshare, 2022)
Additional file 5: Figure S5. Composition of splenic immune cells and CD4+ T cell subpopulations in healthy Sigirr +/+ mice and Sigirr −/− mice. (A), Frequencies of major immune populations in spleens between Sigirr +/+ mice (n = 5) and Sigirr −/− mice (n = 5). (B), Absolute number and frequency of granulocytes among 2.5 × 105 live CD45+ leukocytes derived from Sigirr +/+ and Sigirr −/−mice. (C), Representative plots of T cells (CD3+ NK1.1−), NK cells (CD3− NK1.1+), NKT cells (CD3+ NK1.1+), B cells (CD3− CD19+), CD4 T cells (CD3+ CD4+ CD8−), CD8 T cells (CD3+ CD4− CD8+), CD11b+ Gr1hi granulocytes and CD11b+ Gr1hi mononuclear phagocytes among live CD45+ leukocytes in Sigirr +/+ and Sigirr −/−mice spleens. (D), Bar graphs representing absolute numbers (left) and frequency (right) of subpopulations among live CD45+ leukocytes as measured by flow cytometry in the spleens of Sigirr +/+ and Sigirr −/−mice. (E–F), Representative plots of naïve (CD62L+ CD44−), effector (CD62L+ CD44−), CD62L+ CD44+ cells and regulatory T cells (CD25+, F) among live CD4 T cells. (G) Absolute number (upper) and frequency (lower) of naïve, effector, CD62L+ CD44+ cells and regulatory T cells among CD4+ T cells in the spleens of Sigirr +/+ and Sigirr −/−mice. (H) Ratio of effector to naïve CD4+ T cells (E/N) between Sigirr +/+ mice (n = 5) and Sigirr −/−mice (n = 5). ns, not significant (P > 0.05), *P < 0.05, **P < 0.01 and ***P < 0.001 and ****P < 0.0001 (unpaired t test).
Keywords: Genetics; Immunology